2002
DOI: 10.1046/j.1365-2214.2002.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Communicating a diagnosis of developmental disability to parents: multiprofessional negotiation frameworks

Abstract: It is a hard task for professionals to give and parents to receive the bad news about a child's developmental disability. This study describes how findings about four preschool children, with difficulties suspected to lie within the autistic spectrum, were negotiated with parents by two multiprofessional groups, one in a Medical (Site M) and one in an Education setting (Site E). Each assessment was undertaken over half a day, the professionals jointly interacting with the child and family. All assessment discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Another line of recent research has looked at interpretive sessions from the perspective of sociolingustic analysis (Abrams & Goodman, 1998; Bartolo, 2002;Gill & Maynard, 1995). These studies have found that there are certain characteristic patterns ofinforming parents of assessment results.…”
Section: Research Literaturementioning
confidence: 98%
“…Another line of recent research has looked at interpretive sessions from the perspective of sociolingustic analysis (Abrams & Goodman, 1998; Bartolo, 2002;Gill & Maynard, 1995). These studies have found that there are certain characteristic patterns ofinforming parents of assessment results.…”
Section: Research Literaturementioning
confidence: 98%
“…A mixed methods French study reported that satisfied families described professionals who made them feel respected, gave them time, and were open minded, direct, and sympathetic,197 whereas harmful practices included not checking to ensure that parents understood the explanation or to see if further time or discussion would be helpful. One qualitative study of how the diagnosis was communicated found that tensions between “realism” and “hopefulness” were negotiated by using a parent friendly frame, complemented by a hopeful formulation or by a defocusing of a “bad news” approach 198. The tension of how optimistic to be when communicating the diagnosis and prognosis was also highlighted in a qualitative study in which parents described feeling more positive than professionals about the prognosis; in turn the professionals described parents as being too optimistic 199.…”
Section: Family Preferences For Asd Diagnostic Assessmentmentioning
confidence: 99%
“…The clarity of the diagnosis that is given,26 and the perceived quality of the information provided during the process,74 are also related to parental satisfaction with the diagnostic process. The nature of communication with professionals during diagnosis is also a predictor of parental satisfaction: the fewer professionals that parents need to see in order to obtain a diagnosis the greater their satisfaction;70 similarly, the perceived professionalism of the person giving the diagnosis is related strongly to satisfaction 27 72 75…”
Section: Diagnostic Practice and Its Impactsmentioning
confidence: 99%